The ESL Teacher as Plurilingual: An Australian Perspective. Issue 3 (16th August 2013) - Ellis, Elizabeth
<x xml:space="preserve">Abstract</x> This article reports a study on a little‐researched area: the linguistic repertoires of teachers of English as a second language (ESL) to adults. It proposes that, to heed recent calls to recognise learners' plurilingualism and to incorporate learners' languages in the ESL classroom, teachers' plurilingualism must be acknowledged and valued. This study investigated the language biographies of plurilingual and monolingual teachers of ESL in Australia and found them to be characterised by a wide range of circumstantial and elective language learning experiences. The effect of different experiences on teachers' knowledge and beliefs about language learning and teaching are presented and discussed, drawing upon literature from language teacher cognition. Plurilingual teachers were found to see language learning as challenging but possible, whereas monolingual teachers associated language learning with their own unsuccessful experiences and saw it as difficult and potentially humiliating. Circumstantial plurilinguals were found to have a wide range of language experiences which contribute to their understanding of familial language use and issues arising from child and adult migration. All the plurilinguals were found to have gained useful insights about language teaching from their own experiences, and the article argues that these should be seen as a resource for systematic reflection in teacher education.